Globalisasi, 'Global Governance' dan Prospek 'Governance' di Dunia Ketiga - Muhadi Sugiono (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
One of the most important theme in the current debates on globalization is the implication of globalization to the state. Two contending positions can immediately be identified: one that argues that globalization results in the 'retreat of the state' and other that argues that globalization is 'what the states make of it'. While it is quite apparent that none of these two positions is satisfactorily defensible, this article presents another problem related to the way in which the state is related to the globalization. Both positions tend to take the state for granted, in that, all states are (western) modern states, without taking into account their history and sociology. As a result, they fail to cacth inside dynamics of political power taking place in the group of states so called the third world and, therefore, lose their releaance.